Whistles in the reeds: a new country record of the deeply divergent Gracixalus medogensis, with additional insights on Gracixalus frogs (Rhacophoridae) in India - Tajo, Tage; K., Radhakrishna Upadhyaya; Sarmah, A. N. Dikshit Akalabya; Garg, Sonali; Biju, S. D. (Zootaxa, 2025)
The poorly known Gracixalus medogensis (Ye and Hu, 1984) was originally described from the Medog region in Tibet, China based on a single specimen. Despite a recently reported new collection from the type locality, knowledge about the species remains limited. During our recent field surveys in the state of Arunachal Pradesh, India, we collected new populations of Gracixalus frogs from Tale Valley Wildlife Sanctuary and Tiwarigaon. These were identified as belonging to G. medogensis based on external morphology and genetic evidence, constituting the first record of the species from India. Our matrilineal genealogy further recovers G. medogensis as having a deeply divergent phylogenetic position distinct from all other congeners. Additionally, we present a detailed morphological redescription of the species using multiple specimens. We also provide first insights into the male vocal repertoire in the species and compare it with call properties of other studied congeners. Furthermore, we report additional locality records in Namdapha National Park for G. patkaiensis, which was so far known as the sole representative of the genus in India. We also expand the knowledge on this species’ morphology, including colour variations, natural history, and habitat use. Our study additionally documents an interesting observation of green blood and turquoise bones in G. patkaiensis, making it the first report of this unique characteristic in a species of frog from India. Finally, our findings highlight the need to further investigate not only the diversity of Gracixalus in the northeastern region of India, but also the phylogenetic relationships among members, particularly of G. medogensis, and of Gracixalus sensu lato at large.